Pengaruh Pendidikan dan Kesehatan Terhadap Produk Domestik Regional Bruto (PDRB) Riau 2010-2012 - Aswanto Aswanto (EXERO : Journal of Research in Business and Economics, 2023)
One of the important indicators to determine the condition of a region/region in a certain period is to be able to see from the Gross Regional Domestic Product (GRDP) data both at current prices and at constant prices. Education is an asset for human resources that can improve capabilities both formally and skills, making it easier for human resources to find work because it has a high competitive value and results in being able to produce a lot of goods and services which ultimately add to a country's gross regional domestic product. region/region. Health is a very important thing. Regions that have a high level of health will be more successful in carrying out economic development and economic growth. Because with health someone is able to work in the economy. Life expectancy is one of the indicators commonly used to determine development plans in the health sector in the future as well as to evaluate health development that has been implemented. This study aims to examine the effect of the level of education (average length of schooling) and health (life expectancy) on the Gross Regional Domestic Product (GRDP) in Riau Province 2010-2021. This study was analyzed using descriptive statistical analysis and multiple regression analysis using the Eviews 10 application. The results of this study found that the level of education (average EXERO, Vol. 06, No. 01, Mei 2023 hal 19 - xx 20 length of schooling) and health (life expectancy) had a positive effect on the province's gross regional domestic product (GDP) Riau 2010-2021.